UAV-LIDAR BORESIGHT ESTIMATION USING VIRTUAL CONTROL POINTS: A CASE STUDY - Machado, M. V. [UNESP]; Tommaselli, A. M.G. [UNESP] (Copernicus Publications, 2023)
UAV-lightweight systems can achieve centimetric accuracy, being a viable alternative for forestry mapping and agriculture. However, they are smaller and more flexible systems, making them more susceptible to error influences than conventional systems. The errors from misalignment between the inertial measurement unit (IMU) and the laser unit, scanning angles, ranges, and the identification of interest features can significantly affect the accuracy of the point cloud. This paper aims to compare two different stochastic models using system raw data for boresight misalignment. Furthermore, to minimise the error in identifying the control point in the point cloud, a technique to create virtual control points is proposed and analysed. These strategies were tested with real flight data, and no significant differences were observed between the two mathematical models in the experiments performed in this study. However, the technique of virtual points enabled an improvement of 13.84% in the results. The accuracy achieved for the point cloud was close to 19 cm in planimetry and 10 cm in altimetry.
Keywords: boresight misalignment; least squares methods; point-to-point approach; UAV-lidar systems; virtual control point